THE RELATIONSHIP BETWEEN PARENTS' EDUCATIONAL ANXIETY AND SCHOOL CHILDREN’S ACADEMIC BURNOUT - SYED CHEAR, SYED LAMSAH; HASSAN, MOHD HANIP; YOUHUI, WANG (Selangor Humaniora Review, 2025)
Educational anxiety has become an important issue in family education. School is an important developmental context for children, but has been criticized for developing harmful psychological disorders such as academic burnout. The objective of this study is to determine the relationship between parents' educational anxiety and children's academic burnout. The study was conducted at a primary school in Hangzhou City in the northern part of Zhejiang Province, China. It involved 150 respondents, consisting of an equal ratio of fathers and mothers of the school children. The result indicated that parents’ education anxiety is at a very high level, whereas the level of children's academic burnout is high. Further analysis reveals that the correlation between Pearson's product "parental educational anxiety" and “school children's academic burnout” was very high, positive, and statistically significant (r = .958, p < .001). This suggests that an increase in parents' educational anxiety will lead to academic burnout for children. The insights gained from this research can be instrumental in making significant changes in classroom practices, parent-children relationships, and school-parent engagement, leading to a healthier and productive academic experience for children.